Barriers and Perceptions of Disabled University Students on Online Learning Methods during the Covid-19 Pandemic - Nurul Aqilah Arifin; Mohd Hanafi Mohd Yasin; Sinta Yuni Susilawati; Rabaishah Azirun (Jurusan Pendidikan Luar Biasa, Fakultas Ilmu Pendidikan, Universitas Negeri Malang, 2023)
The purpose of this study is to find out in more detail about the obstacles faced by students with OKU UKM while following online learning as well as their views in particular on effective online learning methods during this pandemic season. Next, the study was conducted quantitatively using survey method. An online questionnaire (google form) was used in this study as a research instrument which in total contains 18 items. The study sample was randomly selected in groups according to the rate for each category. It consists of 30 OKU students from 47 OKU students who are active in the 2021/2022 study session at UKM. Data collection was through a questionnaire and the findings were analyzed by descriptive analysis using Statistical Package for Social Sciences for Windows Version 26 (SPSS) software. The statistics used for data analysis in the study were mean score, standard deviation, frequency and percentage. The findings of the study have shown that the majority of barriers faced by students with disabilities during online PdP during the Covid-19 pandemic season were barriers in completing group assignments with a high level. Furthermore, the level of the overall barriers faced by students with disabilities is at a moderate level. As for the views of OKU students, the majority of OKU students are very affected by the Covid-19 pandemic. While the effective PdP method for students with disabilities during the pandemic season varies. In conclusion, the effective mode of learning and teaching for OKU UKM students during the pandemic season depends on the type of disability of the OKU students.